Gender and Health Status Response to Long-Term Oxygen Therapy in COPD Patients - Coleta, Karina Dela [UNESP]; Lima, Daniela F. [UNESP]; Tanni, Suzana E. [UNESP]; Silveira, Liciana V.A. [UNESP]; Godoy, Ilda [UNESP]; Godoy, Irma [UNESP] (Elsevier, 2011)
Introduction: The association of gender with health status (HS) response to long-term oxygen therapy (LTOT) in very severe COPD is unclear. The aims of this study were: (1) to compare dyspnea perception and HS between male and female with very severe COPD at baseline and (2) to provide a prospective assessment of HS response to LTOT, according to gender. Patients and methods: Hypoxemic COPD (n = 97, age: 65.5 ± 9.6 years, 53% males) were enrolled in a prospective longitudinal study over 12 months or until death. St. George's Respiratory Questionnaire (SGRQ) and baseline dyspnea index (BDI) were assessed. Results: At baseline, HS impairment and dyspnea sensation were similar between genders. After 12 months of LTOT, women presented improvement in symptom (64.1 ± 20.6 versus 40.6 ± 22.9; P<0.0001) and total SGRQ scores. Men also showed improvement in symptoms after 12 months (62.7 ± 23.3 versus 49.6 ± 22.8; P<0.0005); however, they presented deterioration of activity, impact and total scores during the study period, with markedly decline of activity domain (68.5 ± 20.0 versus 75.9 ± 16.9; P=0.008). BDI did not show significant difference by gender over the study period. Conclusions: Our results show that the HS course in very severe COPD patients differs according to gender, as females show greater response longitudinally to LTOT. © 2010 SEPAR.
Asociación del sexo con el estado de salud en respuesta a la oxigenoterapia crónica domiciliaria en pacientes con enfermedad pulmonar obstructiva crónica
Keywords: COPD; Gender; Health status; LTOT